Economical and Technical Challenges of a Large Scale Solar Plant - YAGCI, Mustafa (International Journal of Intelligent Systems and Applications in Engineering, 2017)
Turkish government has increased the importance of Konya-Karapınar region by making the area a pilot region for solar energy production.  In the near future, the government plans to have a 4 GW solar energy plant in the area.  According to this master plan, a pilot solar energy production system was established in the Necmettin Erbakan University campus.  A 1000W two-axis tracking and 1000W fixed panels were implemented in this system. In this paper, the performance of these panels are compared and evaluated.  25 years of solar radiation data for Konya is taken from the state meteorology institute, and the produced energy is compared with the predicted values.  Tracking panels are found to be approximately 25% more efficient than the fixed panels.  However, the maintenance of the tracking panels is observed to be more costly.  Moreover periodic cleaning and repairs are found to be very important and another cost factor for both systems.  Using the insight from this pilot system, an economic analysis of a large scale 1MW solar energy plant to be established in the campus is performed.  For this analysis, fixed panels are considered due to the low investment and maintenance costs and the simplicity of the maintenance work.  It is found that the 1MW solar plant will recover the investment cost within 7-8 years and will provide almost 3M$ profit after 20 years.